The Duchess of Padua - Wilde, Oscar, 1854-1900 (Salt Lake City, UT : Project Gutenberg, 1997)
"The Duchess of Padua" by Oscar Wilde is a five-act tragedy written in 1883. Set in Renaissance Italy, this blank verse drama follows Guido Ferranti, a young man who arrives in Padua to avenge his father's murder at the hands of the Duke. His mission becomes complicated when he falls deeply in love with the Duke's wife, Beatrice. As passion collides with vengeance, both lovers make fatal choices that bind them in tragedy, leading to devastating consequences neither anticipated. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/The_Duchess_of_Padua
Release date is 1997-04-01
Transcribed from the 1916 Methuen and Co. edition by David Price
Keywords: Tragedies (Drama); Revenge -- Drama; Padua (Italy) -- Drama; English drama -- 19th century